The effect of periodontal therapy on cardiovascular risk markers: a 6-month randomized clinical trial - Caúla, André Luis; Lira-Junior, Ronaldo; Tinoco, Eduardo Muniz Barretto; Fischer, Ricardo Guimarães (Journal of clinical periodontology, 2014)
Aim To determine the influence of non‐surgical mechanical periodontal treatment on inflammatory markers related to risk for cardiovascular disease. Material and Methods A total of 64 patients with severe chronic periodontitis was randomly subjected to immediately periodontal treatment (test group, n = 32) or delayed periodontal treatment, without treatment during the study period (control group, n = 32). Clinical periodontal and laboratory examinations were performed at baseline (T0), 2 months (T2), and 6 months (T6) after the initial examinations (Control group) or completion of periodontal treatment (Test group). Results After 2 months of periodontal treatment there was a significant reduction of erythrocyte sedimentation rate (ESR) and triglycerides (p = 0.002, p = 0.004, respectively) in the test group. Median values of C‐reactive protein, ESR, total cholesterol, and triglycerides were reduced after 6 month of periodontal treatment in the test group (p < 0.001, p < 0.001, p < 0.001, and p = 0.015, respectively). Conclusions The non‐surgical periodontal treatment was effective in reducing the levels of systemic inflammation markers and improved the lipid profile in subjects with severe chronic periodontitis.